A review on α-glucosidase inhibitory activity of first row transition metal complexes: a futuristic strategy for treatment of type 2 diabetes. Issue 19 (20th April 2022) - Sohrabi, Marzieh; Binaeizadeh, Mohammad Reza; Iraji, Aida; Larijani, Bagher; Saeedi, Mina; Mahdavi, Mohammad
Abstract : Type 2 diabetes mellitus (T2DM) is characterized by high blood glucose levels and has emerged as a controversial public health issue worldwide. Abstract : Type 2 diabetes mellitus (T2DM) is characterized by high blood glucose levels and has emerged as a controversial public health issue worldwide. The increasing number of patients with T2DM on one hand, and serious long-term complications of the disease such as obesity, neuropathy, and vascular disorders on the other hand, have induced a huge economic impact on society globally. In this regard, inhibition of α-glucosidase, the enzyme responsible for the hydrolysis of carbohydrates in the body has been the main therapeutic approach to the treatment of T2DM. As α-glucosidase inhibitors (α-GIs) have occupied a special position in the current research and prescription drugs are generally α-GIs, researchers have been encouraged to design and synthesize novel and efficient inhibitors. Previously, the presence of a sugar moiety seemed to be crucial for designing α-GIs since they can attach to the carbohydrate binding site of the enzyme mimicking the structure of disaccharides or oligosaccharides. However, inhibitors lacking glycosyl structures have also shown potent inhibitory activity and development of non-sugar based inhibitors is accelerating. In this respect, in vitro anti-α-glucosidase activity of metal complexes has attracted lots of attention and this paper has reviewed the inhibitory activity of first-row transition metal complexes toward α-glucosidase and discussed their probable mechanisms of action.